TINJAUAN KRIMINOLOGI TERHADAP TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN YANG DILAKUKAN OLEH ANAK DI KEPOLISIAN SEKTOR KANDIS - M. Hafiz Asyari; Emilda Firdaus; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Theft is an act of crime, which is very disturbing to the comfort of the community,therefore a consistent action that can enforce the law, so that harmony is established, whichin this case increases theft with violence committed by children. Lots of children commitvarious criminal acts such as theft, rape, persecution and many more. Therefore, the authorsreview in terms of criminology the crime of theft: 1) What are the factors that trigger therampant Crime of Theft with the Giving done by children in the Sector Police Kandis 2) Whatis the legal effort in overcoming the theft of crimes with the grievances committed by childrenin the Kandis Sector Police,This type of research can be classified into the type of sociological juridical research,because in this study the author immediately conducts research on the location or placeunder study in order to provide a complete and clear picture of the problem under study. Thisresearch was conducted in Kandis Sector Police, while the population and samples were allparties related to the problems examined in this study, data sources used, primary data,secondary data, tertiary data, data collection techniques in this study with 2 methods namelyinterviews and literature review.From the results of the problem research there are two main things that can beconcluded. First, there are internal and external factors that cause criminal acts of theft byweighting carried out by children. Internal factors are the level of education, the work ofparents of principals, and individual behavior while external behavior is a factor of theeconomy, social environment, weak law enforcement and factors of opportunity. Second, 2.Efforts to combat theft with weighting carried out by the Sektor Kandis Police, namely: Preemptiveefforts are efforts to improve the moral values of society through extension activitiesor socialization to schools or the general public. Preventive efforts are a continuation of preemptiveefforts that emphasize eliminating opportunities for people to commit theft. Andrepressive efforts are to take action against the perpetrators in accordance with their actionsand fix them and commemorate them so that they are aware and do not repeat again bybringing to the police station and also bringing parents to the Kandis Sector Police. parentsshould always supervise, guard and prevent any deviant acts carried out by children. Second,Members of Kandis Sector Police must create interesting ideas in conducting counseling toschool schools so that children understand and have legal awareness.Keywords: Criminology - Theft - Children